IMPLEMENTASI PERAMALAN DOUBLE EXPONENTIAL SMOOTHING PADA KASUS KEKERASAN ANAK DI PUSAT PELAYANAN TERPADU PEMBERDAYAAN PEREMPUAN DAN ANAK - Riyadhul Fajri; Teuku Muhammad Johan (Jurnal Ecotipe (Electronic, Control, Telecommunication, Information, and Power Engineering), 2017)
The high number of cases of violence in children today is increasing. Among the cases of child abuse are physical torture, sexual harassment and neglect. Every year violence in children increases with different patterns of behavior. Various efforts were made by the government to campaign for child protection legislation. To forecast an increase or decrease in child abuse patterns over the next 5 years, an inhalamanation-based forecasting system is needed. This inhalamanation system is expected to predict how many cases of child abuse that occur from the time in the future. Double expoential smoothing method is the most widely used method to determine the equation of second smoothing data trend through smoothing process. This forecasting system captures the pattern of past data then used to project future data. The purpose of this system is to provide an idea of ??the level of violence in children. The variables used in this system are the types of cases of domestic violence / Traumatic cases of Persecution, Kidnapping cases, Rape cases and Sodomy case types. The case of violence predicted for four years previous year is in 2012, 2013, 2014, 2015. Then processed using the method of double expnential smoothing by looking for the equation of the trend first and followed by looking for second smoothing and forecasting results of the type of violence in the next year that is 2016. The special target of this forecasting system is to project a pattern of child abuse that is still frequent and predict patterns of violence in children for the next few years. This is done to prepare everything needed to handle cases of violence in the future. Long-term goal to predict the level of violence in children for the next 10 years. This is expected to anticipate the acts of violence that occur in children by looking at previous forecasting data.